2019
DOI: 10.1136/jech-2019-212295
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional community correlates of married women’s experiences of male intimate partner physical violence in Bangladesh: a cross-sectional study

Abstract: BackgroundIn Bangladesh, little is known about community-level factors shaping married women’s experiences of male intimate partner physical violence (MIPPV); it is also unknown if these factors interact with each other. We examined the (1) association between four residential community characteristics defined by the attributes of ever married women in those communities–younger age, lower education, higher participation in earning an income and poverty; and (2) two-way interactions between these community-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Using standardization addressed the rightly skewed poor community variable. This approach is consistent with earlier research [17,46].…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Using standardization addressed the rightly skewed poor community variable. This approach is consistent with earlier research [17,46].…”
Section: Methodssupporting
confidence: 93%
“…They may also unable to provide social support and networks for women to resist and men to stop perpetrating violence [28]. In Bangladesh, a study [20] examining the effect of communitylevel factors found that community average per capita household income was a protective factor for physical or sexual IPV, although that association was marginally significant, while another study [17] examined but did not find association between community-level poverty and physical IPV, rendering the association between community-level poverty and IPV inconclusive. Given the lack of empirical evidence using nationally representative data, we wanted to examine whether the interaction between women's intersectional social locations and community types affect their experiences of physical IPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes a range of articles from the 172 reviewed; these included autoethnographic (Ashlee et al, 2017), ethnographic (Sharp, 2021) and narrative accounts (de Regt, 2017), qualitative interview-based studies (Meier, 2020; Peretz, 2017; Thorjussen and Sisjord, 2020), quantitative survey designs (Lord et al, 2019; Rahman et al, 2020) and analysis of secondary data (Earnshaw et al, 2021; Ugidos et al, 2020). Table 2 also identifies the main intersectionality-related findings in the selection of studies, highlighting how each study could be grouped together in different ways around engagement with intersectional methods (Ashlee et al, 2017; de Regt, 2017; Wiens et al, 2020), the use of intersectionality to contribute new insights in a disciplinary field or context of study (Lord et al, 2019; Thorjussen and Sisjord, 2020), to better understand social injustices or inequality (Meier, 2020; Rahman et al, 2020; Ugidos et al, 2020), or to engage in acts of resistance or liberation (Ashlee et al, 2017; Peretz, 2017). We explore in greater detail how and why some of these articles adopt additive thinking and articulation relational frames in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…The Israeli GM society, led by the former IGM president, states that trauma is less common in women on its webpage, reflecting a lack of understanding of the prevalence and consequences of childhood abuse and adult-life violence experienced by women [ 76 ]. Only one IGM member, Gillian Einstein, addresses violence in her scientific work [ 77 ] and public appearances.…”
Section: Methodsmentioning
confidence: 99%